Shaping the foundation of the SuperCyberKids Learning Framework: a comprehensive analysis of cybersecurity education initiatives - Manganello, Flavio; Earp, Jeffrey; Fante, Chiara; Bassi, Giorgia; Fabbri, Stefania; Matteucci, Ilaria; Vaccarelli, Anna; Olesen, Nina; de Vibraye, Arnaud; Callaghan, Peadar; Gentile, Manuel (Frontiers in Education, 2024)
In the rapidly evolving digital landscape, cybersecurity education for children is paramount. The 'SuperCyberKids' project, funded under the EU Erasmus+ programme, aims to address this need by developing a comprehensive educational ecosystem for children aged 8 to 13 and their teachers. Central to this initiative is the SuperCyberKids Learning Framework (SCKLF), which incorporates a game-based approach to enhance engagement and motivation through a bespoke digital learning platform and broader ecosystem. This paper focuses on the second pillar of SCKLF, a detailed survey of 65 cybersecurity education initiatives, offering a practical perspective on the current state of cybersecurity education. The survey covered initiatives within and beyond the European Union, emphasizing the target age group. The analysis of these initiatives provides invaluable insights into the practical application of cybersecurity education and plays a crucial role in shaping the SCKLF. By highlighting the diversity of approaches and strategies in cybersecurity education, this research contributes to a more holistic and applied perspective, ensuring the framework's relevance and effectiveness in fostering digital resilience among young learners.